Long‐term outcomes of surgical management of rectal prolapse. Issue 6 (13th May 2019) - Ng, Zi Qin; Levitt, Michael; Tan, Patrick; Makin, Gregory; Platell, Cameron
Abstract : Background: Various surgical options for rectal prolapse are available but none have been shown to be clearly superior. The aims of this study were to investigate the long‐term recurrence rate of a variety of surgical approaches, their associated morbidities and the types of reoperation used to treat recurrence. Methods: A retrospective analysis was performed of all cases of rectal prolapse surgery within one colorectal surgical unit between January 2000 and June 2017. Abdominal approaches consisted of rectopexy (RP) and resection rectopexy (RRP); perineal approaches included perineal rectosigmoidectomy (PR) and Delorme's repair (DR). Complications were graded according to the Clavien–Dindo classification. The median follow‐up was 4.5 years (interquartile range 1.5–10.1, maximum 16.5). Statistical analysis was performed using Kaplan–Meier to determine recurrence rates. Results: A total of 157 patients were included in the study. The numbers for each procedure were: DR ( n = 55), RRP ( n = 44), RP ( n = 38) and PR ( n = 20). The majority were females (94%). The perineal group were significantly older than the abdominal group (80 versus 67 years, P = 0.0001). At 5 years, the recurrence rates were 52%, 30%, 5% and 3% for DR, PR, RP and RRP, respectively. Morbidity was highest in PR (20%) followed by RRP (18%), RP (16%) and DR (7%) (n.s.). The overall morbidity rates for perineal group and abdominal group were 10.7% and 17.1%, respectively (n.s.). Conclusion: Abdominal approaches have a significantly lower recurrence rate at 5 years but tend to be associated with higher morbidity. Abstract : The studies on the repair of rectal prolapse have produced conflicting outcomes. This study reviewed the long‐term outcomes of abdominal and perineal approaches for the repair of rectal prolapse in a single colorectal unit.